Mild traumatic brain injury increases vulnerability to post-traumatic stress disorder in rats and the possible role of hippocampal DNA methylation - Niu, Yujie; Cai, Zhibiao; Cheng, Junkai; Zhou, Jie; Qu, Xiaodong; Li, Changdong; Zhang, Zhongjing; Zhang, Shenghao; Nan, Yaqiang; Tang, Qifeng; Zhang, Lei; Hao, Yelu (Frontiers in Behavioral Neuroscience, 2025)
IntroductionClinical studies have established that patients with mild traumatic brain injury (mTBI) are at an increased risk for developing post-traumatic stress disorder (PTSD), suggesting that mTBI increases vulnerability to subsequent PTSD onset. However, preclinical animal studies investigating this link remain scarce, and the specific biological mechanism through which mTBI increases vulnerability to PTSD is largely unknown.MethodsIn this study, we modeled mTBI in rats using a mild, closed-head, weight-drop injury, followed 72 h later by exposure to single prolonged stress (SPS) to simulate PTSD. Then, we investigated the impact of mTBI on subsequent PTSD development by observing the behaviors of rats in a series of validated behavioral tests and further explored the possible role of hippocampal DNA methylation.ResultsWe found that, compared with rats in the PTSD-only group, those in the mTBI + PTSD group exhibited higher anxiety levels, higher depression levels, and impaired spatial learning and memory as determined in the open field test, the forced swimming test, and the Morris water maze test, respectively. Rats in the mTBI + PTSD group also exhibited higher hippocampal DNMT3b protein expression compared with those in the PTSD group.ConclusionIn conclusion, our results demonstrated that mTBI increases vulnerability to PTSD in rats, possibly through alterations in hippocampal DNA methylation patterns.